Florez, F. (1983). La Etica de Meister Eckhart, Colección 'Universitas Philosphica' No. 2, Facultad de Filosofía, Pontificia Universidad Javeriana, Bogotá. - Editor, El; Pontificia universidad Javeriana (2016)
null